Perancangan dan Penempatan Alat Pemadam Kebakaran Jenis Sprinkler - Iqbal Hayes Gavrela; Aditya Firmansyah A. P; Krisna Adiarta H. K; Rama Noel Damita Simanungkalit; Dika Ayu Safitri (International Forum of Researchers and Lecturers, 2024)
The fire suppression ability of this sprinkler installation compared to other fire extinguishing equipment has been proven to be more effective. Because the sprinkler system does not require an operator when operating, fires can be prevented earlier before causing greater losses. For this reason, the implementation of sprinkler systems in buildings is crucial. According to KEPMEN PU NO. 10/KPTS/2000, a building must have elements that can maintain structural stability to a certain level during a fire. This research was conducted directly in the field, and the necessary data was obtained independently through interviews with relevant parties. The author conducted research observations in the archive warehouse to obtain both primary and secondary data. Primary data included field documentation and calculations. Planning calculations were done directly by calculating the number of sprinklers, water requirements, and reservoirs to determine the precise needs. Based on the survey, it was found that the size of the archive warehouse is 48 x 48 m, totaling 2304 m2. The maximum distance between sprinklers used was 4.6 m. Therefore, the effective distance between sprinkler heads is 193 units. The result of the calculation for the water supply for the sprinkler system obtained 34,139.77 liters, with the total overall cost for the equipment and materials used being Rp. 63,121,925.74. Based on the data and calculation results regarding the planning and design of fire protection equipment in open active spaces adhering to the NFPA-13 Standard for the Year 2019, it is expected to provide comfort and safety against the threat of fire incidents.